(3SjGSGJ hGSJQGJjLjGJ GdGYeGds - (3YHO GdSdGe(B, (3GHh bMas ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2004)
(3gPG GdcJGH (B: (3ebOeI hbVGjG CSGSjI , GdJZjQGJ hGdJMhdGJ aj HjFI GdGYeGd aj Xd GdYhdeI , GdYhdeI hGdeSDhdjI GdchfjI defTCJ GdGYeGd , GdYhdeI gd gj XGgQI cdjI Ce LRFjI , SjGSGJ GdGYeGd Gdeaghe hGdGgejI GdfSHjI hfWGb GdOQGSI HfGA heQGLYI SjGSJ GdGYeGd GdGSJQGJLjGJ , GdGSJQGJLjGJ GdGQcGf GdCSGSjI hGdeSJhjGJ hfeGPL GdHfGA JMOjO GdbhI GdOGaYI ddefXeI hJfejI GdHOGFd GdGSJQGJLjI ,GdGSJQGJLjGJ GdGfhGY hGdeLGdGJ , JfajP hJbjje GdGSJQGJLjGJ , ddeOjQjf hQLGd GdGYeGd GdHfGA ef CLd GdGSJeQGQ , GdOjeheI , SjGSGJ feGPL JOhjd GdfTGW , GdJMGdaGJ GdGSJQGJLjI Hjf GdTQcGJ GdGSjh YQHjI GdWQjb GdQGHY SjGSGJ hGSJQGJLjGYJ GdGSJMhGPhGdGfOeGL aj Xd GdYhdeI , NWW hSjGSGJ GOGQI GdGReGJ , GOGQI GdGReGJ , eONd GdJNWjW dGOGQI GdGReGJ , CeKdI dGReGJ heTcdGJ ef GdhGbY hGdGSGdjH GdJj GSJNOeJ dMdgG (B.s
Keywords: (3EOGQI GdCYeGds; (3GdYhdeIs